Phytochemical Analysis and in vitro Antibacterial Activities of Seagrass Enhalus acoroides against Staphylococcus aureus - Desy Setyoningrum; Ade Yamindago; Syarifah Hikmah J. S; Maftuch Maftuch (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Several studies of marine bioactive compounds have been carried out using seagrass. Enhalus acoroides is a type of seagrass that has bioactive compounds including alkaloids, flavonoids, tannins, steroids, and saponins that have potential as an antibacteria. The aim of study is to investigate the phytochemical compound contained in the crude extract of Enhalus acoroides and its antibacterial activities of Enhalus acoroides against Staphylococcus aureus. The seagrass was collected, washed, dried, grind and exposed to extraction by vacum rotary evaporator at temperature of 40°C and was analyzed for their phytoconstituents. Further, the crude extract was tested against pathogenic bacterial at different concentrations using disc diffusion method to determine the effect of bioactive compounds in E. acoroides to bacteria. In the present study, qualitative test of phytochemical from ethanol extract of Enhalus acoroides leaves contained phytochemical compound of alkaloids, flavonoids, tannins, steroids and saponins, while the extract of roots contained all of compounds except saponins. Based on research can be concluded, that Enhalus acoroides also has antibacterial activity against Staphylococcus aureus that showed by the presence of inhibition zone. The present finding suggests that the extract of seagrass Enhalus acoroides can be used an antibacterial agent from marine